Energy Harvesting for Wireless Sensing and Flexible Electronics Through Hybrid Technologies - Iqbal, Muhammad (Institution of Engineering & Technology, 2023)
Harvesting biomechanical energy is a viable solution for sustainably-powering wearable electronics for continuous medical health monitoring, remote sensing, and motion tracking. This book discusses vibration-based piezoelectric, electromagnetic and hybrid energy harvesters, and addresses their modelling, fabrication and characterization
Description based on publisher supplied metadata and other sources